Analisis Value Added Olahan Cokelat Batangan Pada CV. Rapoviaka Simple Di Kota Palu - Sintya Puspita Sari; Sulaeman Miru; Asngadi Asngadi; Wiri Wirastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
CV. Rapoviaka Simple is one of the MSMEs in the chocolate processing industry that processes semi-finished products into finished products in the form of chocolate bars with various flavors. This shows an effort to increase the added value in the chocolate processing process. This study aims to determine and analyze the amount of added value obtained from processing semi-finished chocolate (block paste) into chocolate bars at CV. Rapoviaka Simple. Data collection techniques in this study through observation and interviews. The data analysis method used is using the hayami method. Based on the results of the study, it shows that processed chocolate bars at CV Rapoviaka Simple provide high added value and profits for producers, with an input of 4kg /day, an output of 4kg/ day is obtained. The amount of added value obtained is Rp 157,188/kg with a value-added ratio of 49.9%, while the profit obtained is Rp 157,188/kg. The return to the owner of the production factor of labor and the contribution of other inputs is 22.72% and 4.73%, so that the company's profit is 72.53%.